Livro de trovas ilustrado - Yanase, Estela Hiromi (2013)
In the present work it is structured the project of an illustrated book of quatrains, authored by Istela Marina de Souza, head of UBT (Brazilian Union of Troubadours) from the city of Bandeirantes, Paraná. It presents the documentation of the entire editorial graphic project involved since the illustration construction and diagramation to the book finishing. The development was based in bibliographic research and testing and sought to develop skills acquired throughout the course of Graphic Design Technology during internalization and professional experiences.